A new and exact map of the dominions of the King of Great Britain on ye continent of North America. Containing Newfoundland, New Scotland, New England, New York, New Jersey, Pensilvania, Maryland, Virginia, and Carolina according to the newest and most exact observations of Herman Moll, Geographer. - Moll, Herman, d. 1732. (Herman Moll; I. King, 1732)
Relief shown pictorially. Depths shown by soundings. Prime meridian: London. Hand-colored. Includes 5 insets: 1. A view of ye industry of ye beavers of Canada . -- 2. A draught of ye town and harbour of Charles-Town -- 3. A map of the principal part of North America -- 4. A map of the improved part of Carolina with the settlements &c. -- 5. [Louisiana and Carolina with the Gulf of Mexico].